An Analysis of Illocutionary Acts in Benjamin Netanyahu Speech - Siti Ifatul Auliyah; Hanif Maulaniam Sholah (Jurnal Pendidikan dan Sastra Inggris, 2026)
This study investigated the types and functions of illocution in some of Benjamin Netanyahu's speeches, focusing on how language was used strategically to influence public opinion and national morality during the Israeli-Palestinian conflict. By using a qualitative approach and classification of John Searle's illocutional acts, namely representative, commissionic, directive, expressive and declarative. This study analyzed transcripts of Benjamin Netanyahu's speeches delivered in 2023, 2024, and 2025. The analysis revealed that there were four types of illocution actions found: representative, commissive, expressive and directive. Representative actions are most often used, especially in situations that are intended to be convincing. This act of speech affirms political positions, strengthens national unity, and influences public perceptions around the world. The study shows how Netanyahu uses language strategically to encourage patriotism, political action, and public behavior. This study expands the field of pragmatism and political discourse analysis, emphasizes the importance of speech in narrative shaping during conflicts, and encourages a more critical understanding of political communication.